The Use of Crustacea Shell Extract as a Biocoagulant in Open Fracture - Nabila, Alifia Ichsan; Indriawati, Ratna (Universitas Muhammadiyah Yogyakarta, 2022)
In recent years, shrimp is one of Indonesia's biggest fisheries export. It is causing a dramatic increase in shrimp shell waste production but yet a minimum way of utilization. Its most valuable material, chitosan, is called the magic of nature for its wide application, especially as a biocoagulant. Chitosan is a natural polysaccharide with a positive ion that can initiate the aggregation of red blood cells around the wound and form a thrombus. Chitosan is isolated from chitin by demineralization and deproteinization process that will determine the degree of deacetylation. Here, we investigate further whether it can effectively work as a biocogulant to control hemostasis in an emergency case like an open fracture. An open fracture is the most serious case of orthopedic injuries with early hemorrhage as one of the main causes of death. We found that gauze with chitosan-based can lessen bleeding without additional compression. In vitro study showed the effect of shortening clotting time that is essential to stop bleeding. The purpose of this literature review is to gain an understanding of the latest research relevant to the use of chitosan extract as a biocoagulant, including national and international articles and journals from 2011-2021 with a narrative method. The results show that chitosan can initiate red blood cell aggregation and shorten the clotting time rate.